Preparation method of corrugated plate type flue gas comprehensive treatment catalyst
By using the method of alternately impregnating corrugated plate-type structure and functional components, a flue gas comprehensive treatment catalyst with high reaction rate and stability was prepared, which solved the problems of low molding rate and insufficient mechanical strength of the existing catalyst, and achieved low cost. Simple process and efficient catalytic effect.
Patent Information
- Application Number
- CN202510031287.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing honeycomb catalysts are prone to cracks or bonds to the mold when the number of processing holes increases, resulting in low molding rate and low mechanical strength, resulting in waste of resources and increased costs.
A flue gas comprehensive treatment catalyst with a corrugated plate structure is used to press glass fiber paper into corrugated paper and alternately impregnate and calcinate with the carrier slurry and functional component liquid to form a catalyst with high reaction spacespeed and stability.
The reaction rate, catalytic activity and stability of the catalyst are improved, and the process is simple and easy to operate, low cost, and the substrate strength is improved, which is suitable for a wider range of application conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of comprehensive treatment of industrial catalytic flue gas, and in particular relates to a method for preparing a corrugated plate type comprehensive treatment catalyst for flue gas. Background Art
[0002] The catalyst is the main part of the flue gas treatment system. Currently, the shaped catalysts are honeycomb, plate, and corrugated. At present, the domestic experiments mainly focus on honeycomb catalysts, which often require the catalyst to be processed into a honeycomb with a larger number of holes to increase its external specific surface area. However, as the number of holes in the honeycomb catalyst increases, higher requirements are placed on the mold. In addition, as the number of holes in the honeycomb catalyst increases, cracks are likely to appear during extrusion or it is easy to stick to the mold, resulting in a low molding rate and low mechanical strength, resulting in a waste of manufacturing resources and increased costs. Therefore, how to provide a denitrification catalyst with a high reaction space velocity and good stability is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0003] In view of this, the present invention aims to overcome the technical defects in the prior art that the catalyst is prone to cracks or sticking to the mold, resulting in low molding rate and low mechanical strength, and proposes a method for preparing a corrugated plate type flue gas comprehensive treatment catalyst.
[0004] To achieve the above object, the technical solution of the present invention is achieved as follows: A method for preparing a corrugated plate type flue gas comprehensive treatment catalyst comprises the following steps: Step S1: impregnating glass fiber paper with a molding liquid and drying the resulting glass fiber flat paper, pressing the glass fiber flat paper into glass fiber corrugated paper, and alternately stacking and bonding the glass fiber flat paper and the glass fiber corrugated paper to obtain a molding skeleton;
[0005] Step S2: immersing the formed skeleton obtained in step S1 in a carrier slurry, drying and calcining the carrier, wherein the carrier slurry includes a titanium source and an auxiliary component source, and the auxiliary component source includes one or more of a zirconium source, a silicon source, a cerium source, and an aluminum source; Step S3: impregnating the carrier obtained in step S2 in a first functional component impregnation solution, and then filtering and calcining to obtain a catalyst precursor, wherein the first functional component impregnation solution includes vanadyl oxalate, ammonium metatungstate and molybdenum nitrate; Step S4: The catalyst precursor obtained in step S3 is impregnated in a second functional component impregnation solution and then reduced and dried to obtain a finished catalyst product, wherein the second functional component impregnation solution includes a noble metal precursor.
[0006] In some embodiments of the present invention, the forming liquid includes silica sol with a mass concentration of 30% to 80%.
[0007] In some embodiments of the present invention, the titanium source includes one or more of titanium dioxide, titanyl sulfate, titanium sulfate, titanium chloride, and titanyl sulfate.
[0008] In some embodiments of the present invention, the zirconium source includes one or more of zirconium oxide, zirconium nitrate, zirconium oxynitrate and zirconium n-propoxide.
[0009] In some embodiments of the present invention, the silicon source includes one or more of sodium silicate, potassium aluminum silicate and potassium silicate.
[0010] In some embodiments of the present invention, the aluminum source includes one or more of aluminum oxide, aluminum hydroxide, aluminum sulfate, aluminum chloride and aluminum nitrate.
[0011] In some embodiments of the present invention, the cerium source includes one or more of cerium nitrate, cerium chloride and cerium sulfate.
[0012] In some embodiments of the present invention, after calcination in step S2, the mass ratio of titanium dioxide to the oxidized auxiliary component source in the carrier is 8:2-6:4.
[0013] In some embodiments of the present invention, the carrier slurry further includes a thickener and a defoamer. In some embodiments of the present invention, the thickener is polyvinyl alcohol, with a mass percentage of 3% to 10%, and in some embodiments of the present invention, the defoamer is a polyether defoamer, with a mass percentage of 0.2% to 1%.
[0014] In some embodiments of the present invention, the first functional component impregnation solution includes the following components in parts by weight: 160-180 parts of vanadyl oxalate, 120-140 parts of ammonium metatungstate, 3-5 parts of molybdenum nitrate, and 1000-1200 parts of water.
[0015] In some embodiments of the present invention, the loading amount of precious metal in the finished catalyst is no more than 0.5%.
[0016] In some embodiments of the present invention, the noble metal in the noble metal precursor is one or more of Pt, Ir, Pd, Ru, and Au.
[0017] In some embodiments of the present invention, the noble metal precursor is tetraammonium platinum nitrate.
[0018] In some embodiments of the present invention, the noble metal precursor is iridium nitrate.
[0019] In some embodiments of the present invention, in step S1, a corrugator is used to press the glass fiber flat paper into glass fiber corrugated paper.
[0020] In some embodiments of the present invention, the wave height of the glass fiber corrugated paper in step S1 is 3 mm-8 mm, and the wavelength is 15 mm-25 mm.
[0021] In some embodiments of the present invention, the corrugated shape of the glass fiber corrugated paper is one or more of triangular, trapezoidal, and square corrugations, preferably triangular corrugations.
[0022] In some embodiments of the present invention, the immersion time in step S2 is 3 min to 5 min.
[0023] In some embodiments of the present invention, the drying temperature in step S2 is 100° C. to 150° C., and the drying time is 2 h to 5 h. In some embodiments of the present invention, the calcination temperature in step S2 is 500° C. to 600° C., and the calcination time is 4 h to 6 h.
[0024] In some embodiments of the present invention, the immersion time in step S3 is 1 min to 3 min.
[0025] In some embodiments of the present invention, the filtration time in step S3 is 30 min to 60 min.
[0026] In some embodiments of the present invention, the calcination temperature in step S3 is 400° C. to 600° C., and the calcination time is 4 h to 8 h.
[0027] In some embodiments of the present invention, the immersion time in step S4 is 3 min to 5 min.
[0028] In some embodiments of the present invention, the drying and reduction time in step S4 is 1 h to 3 h.
[0029] Compared with the prior art, the present invention has the following advantages: (1) The present invention improves the corrugated plate structure of the catalyst and the formulation of the active components, so that the prepared catalyst has the advantages of higher reaction space velocity, high catalytic activity, good stability, etc., and has the advantages of simple preparation process and easy operation, etc.
[0030] (2) The present invention uses glass fiber board as the substrate, which is low in cost and cheaper than the existing stainless steel wire mesh as the substrate. The thickness can be adjusted as needed, and the shape of the corrugated board can be adjusted according to the reactor conditions, which can improve the strength of the substrate and have a wider range of application conditions; (3) The catalyst prepared by reducing a small amount of precious metal precursor in the second functional component impregnation solution has stronger redox ability and can provide higher catalyst activity.
[0031] (4) After the glass fiber paper is cured by the molding liquid prepared in the present invention, a skeleton is formed, which can significantly increase the strength of the corrugated plate catalyst and make it more resistant to wear.
[0032] (5) The present invention is easy to industrialize, has little environmental pollution, low cost, high production efficiency, and has great value for promotion and application. DETAILED DESCRIPTION
[0033] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0034] Unless defined otherwise herein, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.
[0035] Where values are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.
[0036] In this document, "multiple" and the like, unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0037] In this document, the terms “preferred” and “more preferred” are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute limitations on the scope of protection of the present invention.
[0038] In this document, the words "further" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.
[0039] In this article, the term "and / or" is a description of the association relationship of objects, indicating that three relationships may exist. For example, A and / or B means: A or B, or A and B.
[0040] The terms “include,” “including,” “have,” “contain,” etc. used in this article are open-ended terms, meaning including but not limited to.
[0041] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0042] The present invention will be described in detail below with reference to the embodiments.
[0043] Example 1
[0044] This embodiment provides a method for preparing a corrugated plate type flue gas comprehensive treatment catalyst, and the specific steps are as follows: (1) Skeleton forming: 500 g of silica sol is added to 500 g of deionized water, and mixed evenly to obtain a silica sol forming liquid with a content of 50%; glass fiber paper is impregnated in the forming liquid, and then the impregnated glass fiber paper is dried to obtain glass fiber flat paper, and the glass fiber flat paper is pressed on a forming device to obtain a triangular corrugated shape with a wave height of 4 mm and a wavelength of 20 mm; finally, a layer of glass fiber flat paper and a layer of glass fiber corrugated paper are alternately stacked and bonded to form a formed skeleton; (2) Carrier preparation: impregnation method Dissolve 80 g of titanium dioxide and 55.07 g of zirconium nitrate in 500 g of water, then add 32 g of 1% by mass polyvinyl alcohol solution and 2 g of a polyether defoamer, stir for 30 min to mix evenly to obtain a carrier slurry, immerse the molded skeleton obtained in step (1) in the carrier slurry for 5 min, then dry at 120 ° C for 4 h, transfer to a calcination furnace and calcine at 580 ° C for 5 h to obtain a carrier with a titanium-zirconium ratio (i.e., the mass ratio of titanium dioxide to zirconium oxide) of 8:2; (3) Loading of the first functional component: impregnation and roasting Add 160 g of vanadyl oxalate, 120 g of ammonium metatungstate, and 3 g of molybdenum nitrate into 1000 g of water and stir evenly to obtain a first functional component impregnation solution; impregnate the carrier prepared in step 2 in the first functional component impregnation solution for 2 min, then filter for 30 min, transfer to a calcination furnace, and calcine at 500 °C for 6 h to obtain a catalyst precursor.
[0045] (4) Loading of the second functional component: impregnation, reduction and drying Add 5.1 g of tetraammonium platinum nitrate into 500 g of water and stir evenly to obtain a second functional component impregnation solution; impregnate the catalyst precursor prepared in step 3 in the second functional component impregnation solution for 3 min, and then reduce and dry for 2 h to obtain a finished catalyst.
[0046] Example 2
[0047] This embodiment provides a method for preparing a corrugated plate type flue gas comprehensive treatment catalyst, and the specific steps are as follows: (1) Skeleton forming: Skeleton material 500 g of silica sol is added to 500 g of deionized water, and mixed evenly to obtain a silica sol forming liquid with a content of 50%; glass fiber paper is impregnated in the forming liquid, and then the impregnated glass fiber paper is dried to obtain glass fiber flat paper, and the glass fiber flat paper is pressed on a forming device to obtain a triangular corrugated shape with a wave height of 4 mm and a wavelength of 20 mm; finally, a layer of glass fiber flat paper and a layer of glass fiber corrugated paper are alternately stacked and bonded to form a formed skeleton; (2) Carrier preparation: impregnation method Dissolve 70 g of titanium dioxide and 74.56 g of zirconium nitrate in 500 g of water, then add 32 g of 1% by mass polyvinyl alcohol solution and 2 g of polyether defoamer, stir for 30 min to mix evenly to obtain a carrier slurry, immerse the formed skeleton obtained in step 1 in the carrier slurry for 5 min, then dry at 120 ° C for 4 h, transfer to a calcination furnace and calcine at 580 ° C for 5 h to obtain a carrier with a titanium-zirconium ratio (i.e., the mass ratio of titanium dioxide to zirconium oxide) of 7:3; (3) Loading of the first functional component: impregnation and roasting Add 180 g of vanadyl oxalate, 140 g of ammonium metatungstate, and 5 g of molybdenum nitrate into 1200 g of water and stir evenly to obtain a first functional component impregnation solution; impregnate the carrier prepared in step 2 in the first functional component impregnation solution for 2 min, then filter for 30 min, transfer to a calcination furnace, and calcine at 500 ° C for 6 h to obtain a catalyst precursor.
[0048] (4) Loading of the second functional component: impregnation, reduction and drying Add 5.1 g of tetraammonium platinum nitrate into 500 g of water and stir evenly to obtain a second functional component impregnation solution; impregnate the catalyst precursor prepared in step 3 in the second functional component impregnation solution for 3 min, and then reduce and dry for 2 h to obtain a finished catalyst.
[0049] Example 3
[0050] The only difference between this embodiment and embodiment 1 is that in step (4), 5.1 g of tetraammonium platinum nitrate is replaced by 4.1 g of iridium nitrate, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0051] Example 4
[0052] The only difference between this embodiment and embodiment 1 is that in step (1), zirconium nitrate is replaced by aluminum hydroxide, the titanium-aluminum ratio (i.e., the mass ratio of titanium dioxide to aluminum oxide) in the carrier is 3:2, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0053] Example 5
[0054] The only difference between this embodiment and embodiment 1 is that in step (1), zirconium nitrate is replaced by cerium nitrate, the titanium-cerium ratio in the carrier (i.e., the mass ratio of titanium dioxide to cerium oxide) is 2:1, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0055] Example 6
[0056] The only difference between this embodiment and embodiment 1 is that in step (1), zirconium nitrate is replaced by sodium silicate, the titanium-silicon ratio (i.e., the mass ratio of titanium dioxide to silicon dioxide) in the carrier is 3:1, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0057] Comparative Example 1 The only difference between this comparative example and Example 1 is that in step (2), the amount of titanium dioxide added is 90 g, the amount of zirconium nitrate added is 28.32 g, the titanium-zirconium ratio of the carrier is 9:1, and the other conditions and parameters are exactly the same as those in Example 1.
[0058] Comparative Example 2 The only difference between this comparative example and Example 1 is that in step (4), 5.1 g of tetraammonium platinum nitrate is changed to 7.5 g, and the other conditions and parameters are exactly the same as those in Example 1.
[0059] Comparative Example 3 The difference between this comparative example and Example 1 is that in step (4), 5.1 g of tetraammonium platinum nitrate is replaced by 10.2 g, and the other conditions and parameters are exactly the same as those in Example 1.
[0060] Comparative Example 4 The only difference between this comparative example and Example 1 is that in step (3), no molybdenum nitrate is added, and the other conditions and parameters are exactly the same as those in Example 1.
[0061] Comparative Example 5 The only difference between this comparative example and Example 1 is that step (4) is deleted and step (3) is: Add 160 g of vanadyl oxalate, 120 g of ammonium metatungstate, 3 g of molybdenum nitrate, and 5.1 g of tetraammonium platinum nitrate into 1000 g of water and stir evenly to obtain a first functional component impregnation solution; impregnate the carrier prepared in step 2 in the first functional component impregnation solution for 2 min, then filter for 30 min, transfer to a calcination furnace, and calcine at 500 °C for 6 h to obtain a catalyst precursor.
[0062] The other conditions and parameters are exactly the same as those in Example 1.
[0063] Comparative Example 6 The only difference between this embodiment and embodiment 1 is that in step (1), the silica sol is replaced by acrylic resin, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0064] Test Case The performance of the catalysts prepared in the examples and comparative examples was measured, and the specific method is as follows: Catalytic activity detection: the reaction system temperature is 200-450℃, the reaction pressure is normal pressure, and the mixed gas space velocity is 15000 h -1 The volume content of the mixed gas is: NO: 800 ppm, CO: 1600 ppm, O2: 3%, H2O: 5%, and balance gas: N2. The total gas flow rate is 1.5 L / min. The gases from each route are mixed by a mass flow meter and finally enter the reactor; the reactor is a stainless steel tube with an inner diameter of 30 mm, which is placed in a three-stage heating vertical tube furnace for heating; the exhaust gas is collected at the sampling port for analysis using a MADUR-GA-60 portable flue gas analyzer.
[0065] Testing of substrate strength: The substrate is placed under a press and the pressure is slowly increased to observe the deformation and pressure values of the substrate in different embodiments and comparative examples.
[0066] The specific test results are shown in Table 1.
[0067] Table 1 Test results
[0068] It can be seen from the above table that the mass ratio of titanium dioxide to the auxiliary component source after oxidation has a direct impact on the activity of the catalyst. The mass ratio of titanium dioxide to the auxiliary component source after oxidation beyond the ratio range of 8:2~6:4 is not conducive to the good dispersion of the active components, which leads to a decrease in catalytic activity and a decrease in nitrogen selectivity; vanadyl oxalate, ammonium metatungstate, and molybdenum nitrate have a synergistic effect. Molybdenum, vanadium, and tungsten jointly construct a multi-center redox system, making the oxygen species on the catalyst surface more active and improving the selectivity of NO. x , CO oxidation activity, and improve the selectivity for N2; mixing the first functional component impregnation liquid with the second functional component impregnation liquid to load the carrier together will lead to a decrease in the number of effective active sites, and also reduce the stability of the active center structure, resulting in a decrease in catalyst stability and service life; when the loading amount of the noble metal active component is greater than or equal to 0.5%, the activity of the catalyst decreases. This shows that when the amount of noble metal is too much, the surfactant cannot assist in dispersing a large amount of noble metal, resulting in agglomeration of noble metals, some active sites are not exposed, and the utilization rate of active sites is low.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a corrugated plate type flue gas comprehensive treatment catalyst, characterized in that: The steps include: Step S1: impregnating glass fiber paper with a molding liquid and drying the resulting glass fiber flat paper, pressing the glass fiber flat paper into glass fiber corrugated paper, and alternately stacking and bonding the glass fiber flat paper and the glass fiber corrugated paper to obtain a molding skeleton; Step S2: immersing the formed skeleton obtained in step S1 in a carrier slurry, drying and calcining the carrier, wherein the carrier slurry includes a titanium source and an auxiliary component source, and the auxiliary component source includes one or more of a zirconium source, a silicon source, a cerium source, and an aluminum source; Step S3: impregnating the carrier obtained in step S2 in a first functional component impregnation solution, and then filtering and calcining to obtain a catalyst precursor, wherein the first functional component impregnation solution includes vanadyl oxalate, ammonium metatungstate and molybdenum nitrate; Step S4: The catalyst precursor obtained in step S3 is impregnated in a second functional component impregnation solution and then reduced and dried to obtain a finished catalyst product, wherein the second functional component impregnation solution includes a noble metal precursor.
2. The preparation method according to claim 1, characterized in that: After calcination in step S2, the mass ratio of titanium dioxide in the carrier to the oxidized auxiliary component source is 8:2-6:
4.
3. The preparation method according to claim 1, characterized in that: The titanium source includes one or more of titanium dioxide, titanyl sulfate, titanium sulfate, titanium chloride, and titanyl sulfate; the zirconium source includes one or more of zirconium oxide, zirconium nitrate, zirconyl nitrate, and zirconium n-propoxide; the silicon source includes one or more of sodium silicate, potassium aluminum silicate, and potassium silicate; the aluminum source includes one or more of aluminum oxide, aluminum hydroxide, aluminum sulfate, aluminum chloride, and aluminum nitrate; the cerium source includes one or more of cerium nitrate, cerium chloride, and cerium sulfate.
4. The preparation method according to claim 1, characterized in that: The first functional component impregnation solution includes the following components in parts by weight: 160-180 parts of vanadyl oxalate, 120-140 parts of ammonium metatungstate, 3-5 parts of molybdenum nitrate, and 1000-1200 parts of water.
5. The preparation method according to claim 1, characterized in that: The loading amount of the precious metal in the finished catalyst is not more than 0.5%; the precious metal in the precious metal precursor includes one or more of Pt, Ir, Pd, Ru, and Au.
6. The preparation method according to claim 1, characterized in that: The molding liquid includes silica sol with a mass concentration of 30% to 80%.
7. The preparation method according to claim 1, characterized in that: The wave height of the glass fiber corrugated paper in step S1 is 3 mm-8 mm, and the wavelength is 15 mm-25 mm; the corrugated shape of the glass fiber corrugated paper is one or more of triangular, trapezoidal, and square corrugations.
8. The preparation method according to claim 1, characterized in that: The immersion time in step S2 is 3 min to 5 min; the drying temperature in step S2 is 100° C. to 150° C., and the drying time is 2 h to 5 h; the calcination temperature in step S2 is 500° C. to 600° C., and the calcination time is 4 h to 6 h.
9. The preparation method according to claim 1, characterized in that: The immersion time in step S3 is 1 min to 3 min; the filtration time in step S3 is 30 min to 60 min; the calcination temperature in step S3 is 400° C. to 600° C., and the calcination time is 4 h to 8 h.
10. The preparation method according to claim 1, characterized in that: The immersion time in step S4 is 3 min to 5 min; the drying and reduction time in step S4 is 1 h to 3 h.
Citation Information
Patent Citations
Preparation method of compound SCR catalyst with zero-valent mercury conversion function
CN101972652A
Cerium-based denitration catalyst with titanium-silicon compound oxide as carrier and preparation and application thereof
CN102101048A
Corrugated carrier used for VOCs removal catalyst and production method of corrugated carrier used for VOCs removal catalyst
CN110639622A
Pt-based catalyst for CO purification as well as preparation method and application of the Pt-based catalyst
CN111185167A
Lightweight low-temperature SCR denitration catalyst and preparation method thereof
CN114682251A
Cited By
Flue gas nitrogen oxide reduction catalyst as well as preparation method and treatment method thereof
CN121130958A
A catalyst for reducing nitrogen oxides in flue gas and its preparation and treatment methods
CN121130958B